2016
DOI: 10.4172/2167-0269.1000208
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of Russian Medical Tourists on German Health Care Services: A Kano Model-Based Analysis

Abstract: Introduction: Medical tourism is a steadily growing market in Germany and has a great value of economic interest. Although the majority of patients come from Russia, little information on the needs and expectations of this patient group exists.Methods: Based on the Kano model which is an established research tool for assessing customer's expectations in industry and healthcare, an online questionnaire was constructed. Based on literature review and an interview with a leading medical tourist agency 15 relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…This implies that providing affordable health care, a sustainable tourism experience alongside medical facilities, and the consideration of risk levels influences the expectations of tourists/travelers, and ultimately impacts their intentions to visit a health resort. These results are in line with the work of Plehn et al [38] in healthcare setups. Improving the health and wellness experience of tourists/travelers at the appropriate levels of their expectations could be an important consideration of health resort services' providers when defining their health resort's sustainability strategies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This implies that providing affordable health care, a sustainable tourism experience alongside medical facilities, and the consideration of risk levels influences the expectations of tourists/travelers, and ultimately impacts their intentions to visit a health resort. These results are in line with the work of Plehn et al [38] in healthcare setups. Improving the health and wellness experience of tourists/travelers at the appropriate levels of their expectations could be an important consideration of health resort services' providers when defining their health resort's sustainability strategies.…”
Section: Discussionsupporting
confidence: 93%
“…Many research works have identified the crucial role of individuals' perception and evaluation in defining behavioral intentions [19,36,37]. More precisely, expectations are discussed in determining tourists' decision-making processes and their likely behavioral intentions in health and medical tourism contexts [1,2,[38][39][40][41]. However, despite the seminal role of expectations, there has been little literature that attempts to empirically examine the role of expectations in determining international health tourists'/travelers' behavioral intentions more precisely in a health resort concept.…”
Section: Introductionmentioning
confidence: 99%
“…Witell et al (2013) declared that the Kano model is an excellent tool to explain the roles of different quality attributes for customers. Plehn et al (2016) further used the Kano model to analyze the medical tourism field and found that this model can efficiently depict key attributes to maintain satisfaction. Materla et al (2019) assured that using the Kano model can transform the voice of the customer into inputs for the design of hospital service.…”
Section: Literature Reviewmentioning
confidence: 99%